Intelligence of ûlû al-Albâb in Transpersonal Psychology Perspective - et. al., Siti Romlah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the Islamic world repertoire of the psychology realm, the term ûlû al-Albâb in the Qur'anic text is mentioned 16 times in different topics, involving human psychology of human life problems. This research aims at describing and revealing the discovery of meaning contract. Through the study of library research with contents analysis, the Intelligence of ûlû al-Albâb is transpersonal psychology, the fourth school of modern psychology uncovering the area of psychology not only in symptom and soul but also in the domain of Ûlûl al-Albâb meaning in al-Qur’an. This transpersonal psychology tries to strengthen and develop human potential because this flow reaches spiritual as studied in Islamic psychology with the terms ‘Ihsan’ and ‘Sufism’.